The First Job Experience and its Career Implications - Joseph A. Raelin (Personnel Administrator, 1983)
This article discusses the findings and specific implications of HR policies from career development research which considers the longitudinal effects of first job experiences. The basic premise is that the initial job experiences and attitudes of young people are critical in shaping their ultimate employment experience. Recommendations offer specific human resource activities that can ensure that the young person gets the most out of his or her early career.
Keywords: J28; J62; J21; E24; O15; 330; Career development; First jobs; Job mobility; Commitment to work; Youth careers; Job satisfaction